Analysis of the Impact of Carbon Emissions and Renewable Energy on Economic Growth in Indonesia - Agustian; Linda Wahyu Marpaung (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study was conducted to analyze the impact of carbon emissions and renewable energy on economic growth in Indonesia. This research uses quantitative methods. Data analysis was carried out using multiple linear regression analysis methods. This study uses time series data from 1990-2020 sourced from worldbank.org. The research variable uses a nominal measurement scale. Data analysis and data testing consist of descriptive statistics, classical assumption test, multiple linear regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and coefficient of determination test (R² test). The results showed that carbon emissions have no effect and are not significant to economic growth with a T value of 1.266 < T table 2.045. Renewable energy has a significant effect on economic growth with a T value of -3.010 < T table -2.045. Carbon emissions and renewable energy have a significant effect on economic growth with an F value of 67.335> F table value of 3.34 and a coefficient of determination of 82.8%.